2021
DOI: 10.1136/bmjopen-2020-044356
|View full text |Cite
|
Sign up to set email alerts
|

Covered stents versus balloon angioplasty for failure of arteriovenous access: a systematic review and meta-analysis

Abstract: IntroductionPatients with end-stage renal disease may require arteriovenous (AV) access in the form of arteriovenous fistulae (AVFs) or arteriovenous grafts (AVGs) for haemodialysis. AV access dysfunction requires intervention such as plain balloon angioplasty or covered stents to regain patency.AimTo systematically review and meta-analyse the patency outcomes of covered stents in failing haemodialysis AV access, compared with balloon angioplasty.MethodsThe review was first registered on the International Pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…21 Supporting Information Table S1 summarizes the literature comparison results. 6,[20][21][22][23] The observation of comparable target lesion primary patency in the FLEX-AV registry relate to those reported by RCTs is remarkable given that inclusion criteria for RCTs are more stringent than those for this allcomers registry. Thus, the results provide reinforcement for the benefit of FLEX VP prior to PTA for vascular access treatment.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…21 Supporting Information Table S1 summarizes the literature comparison results. 6,[20][21][22][23] The observation of comparable target lesion primary patency in the FLEX-AV registry relate to those reported by RCTs is remarkable given that inclusion criteria for RCTs are more stringent than those for this allcomers registry. Thus, the results provide reinforcement for the benefit of FLEX VP prior to PTA for vascular access treatment.…”
Section: Discussionmentioning
confidence: 85%
“…6,[19][20][21][22] Ng et al reviewed seven studies that reported a cumulative 1147 subjects (867 AVGs, 280 AVFs) with a range of target lesion patency at 6 months of 8%-34% for subjects treated with PTA. 20 Liao et al conducted a meta-analysis of 11 RCTs PTA in AVF that pooled 976 subjects and reported 6-month patency of 51.7% (236/489) for a PTA cohort. 6 A study by Hu et al conducted a meta-analysis of 18 RCTs of DCB versus PTA in AVF that pooled 1898 subjects with the PTA cohort associated with a 6-month primary patency of 58.6% (499/851).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include stents, with stent grafts appearing to have the most favorable outcomes in our analysis. Stent grafts have also been previously shown to be more effective in the treatment of lesions in AVFs and AVGs, as compared to bare metal stents and angioplasty alone [ 12 15 , 21 23 ]. Stent grafts can be constructed from various materials (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The patency rate in our study was also similar to that in previous studies, which ranged from 67% to 82% patency at 3 months. 11,12,16 To improve AVF patency, many devices, including drug-coated balloons, 17 covered stents, 18 and drug-eluting stents, 19 have been developed and published, but more evidence is still needed. In addition, this study also analyzed the risk factors associated with patency and showed that aneurysm size, the use of drugs, and comorbidities were not associated with patency.…”
Section: Acknowledgmentsmentioning
confidence: 99%